Fresno Mayoral Candidates Debate at Fresno Memorial Auditorium - Watkins, Howard::::::::: (1989)
Tribute to Fresno native, writer and playwright William Saroyan (1908-1981) (Tulare and Van Ness) Chester Rowell Monument to the right